A tandem-locked fluorescent NETosis reporter for the prognosis assessment of cancer immunotherapy - Cheng, Penghui (2023)
NETosis, the peculiar type of neutrophil death, plays important roles in pro-tumorigenic functions and inhibits cancer immunotherapy. Non-invasive real-time imaging is thus imperative for prognosis of cancer immunotherapy yet remains challenging. Herein, we report a Tandem-locked NETosis Reporter 1 (TNR1 ) that activates fluorescence signals only in the presence of both neutrophil elastase (NE) and cathepsin G (CTSG) for the specific imaging of NETosis. In the aspect of molecular design, the sequence of biomarker-specific tandem peptide blocks can largely affect the detection specificity towards NETosis. In live cell imaging, the tandem-locked design allows TNR1 to differentiate NETosis from neutrophil activation, while single-locked reporters fail to do so. The near-infrared signals from activated TNR1 in tumor from living mice were consistent with the intratumoral NETosis levels from histological results. Moreover, the near-infrared signals from activated TNR1 negatively correlated with tumor inhibition effect after immunotherapy, thereby providing prognosis for cancer immunotherapy. Thus, our study not only demonstrates the first sensitive optical reporter for noninvasive monitoring of NETosis levels and evaluation of cancer immunotherapeutic efficacy in tumor-bearing living mice, but also proposes a generic approach for tandem-locked probe design.